Integration of GeoGebra in Learning Mathematics: Benefits and Challenges - Batiibwe, Marjorie Sarah Kabuye (East African Journal of Education Studies, 2024)
Technology is recognized as a vital component of modern society, making it essential for education to incorporate various technological aspects into the teaching and learning of mathematics. GeoGebra is a valuable tool that has gained attention, which enhances mathematics instruction, particularly in areas like geometry, algebra, and statistics. However, there is limited understanding of the benefits and challenges associated with using GeoGebra in mathematics instruction. Therefore, the purpose of this paper was to review existing literature on the benefits and challenges of integrating GeoGebra in a mathematics classroom. Data were collected through a documentary review and to this effect, 53 articles from four databases namely ERIC, Scopus, JSTOR, and ProQuest were reviewed. After analyzing the data through content analysis and categorization, the results revealed that GeoGebra: demystifies mathematical concepts for learners; improves learners' mathematical abilities and representation skills; enhances students’ active construction of knowledge; boosts students’ mathematical achievement; improves students’ attitudes and perceptions toward mathematics learning; empowers students to visualize abstract mathematical concepts; creates an enjoyable learning environment; and fosters the development of 21st-century skills among learners. Nevertheless, the integration of GeoGebra in mathematics instruction presents several challenges. These include teachers' lack of proficiency in using ICT, insufficient training in ICT, limited access to technological equipment, inadequate guidance on interpreting GeoGebra outputs, a high student-to-teacher ratio, and time constraints. Despite the many benefits of GeoGebra, teachers must receive adequate training to equip them with the knowledge and skills necessary to effectively integrate this tool into their teaching and learning of mathematics